Skirting or Courting Controversy? Chinese FDI in Latin American Extractive Industries - Adriana Erthal Abdenur (Revue Internationale de Politique de Développement)
China has become a key player in the development sector in Latin America and the Caribbean (LAC), not only due to trade but also because of the growing scope and visibility of its foreign direct investments (FDI). However, Chinese investments in the region are far from homogeneous, not only oscillating over time and space, but also varying across modes of incorporation into LAC economies. In the extractive industries, Chinese actors rely on a wide gamut of strategies to open up markets and to help ensure access to oil and minerals. This chapter breaks down the concept of FDI into three umbrella categories—greenfield projects, mergers and acquisitions, and joint ventures—to analyse how Chinese capital enters LAC extractive sectors. The chapter argues that, faced with a relatively unfamiliar landscape and new sources of uncertainty, Chinese companies tend to ‘test the water’ through mergers and acquisitions, as well as joint ventures, before delving into greenfield activities like direct mining or drilling. This cautious approach signals a degree of institutional learning on the part of Chinese stakeholders, as well as the desire to avoid charges of neo-colonialism, imposed dependency, and lax adherence to formal regulations.